Fractional solitons: New phenomena and exact solutions - Zeng, Huajun; Wang, Yuxia; Xiao, Min; Wang, Ying (Frontiers in Physics, 2023)
The fractional solitons have demonstrated many new phenomena, which can not be explained by the traditional solitary wave theory. This paper studies some famous fractional wave equations including the fractional KdV-Burgers equation and the fractional long-water-wave equation by a modified tanh-function method. The solving process is given in details, and new solitons can be rigorously explained by the obtained exact solutions. This paper offers a new window for studying fractional solitons.